IDENTIFIKASI TUMBUHAN RIMPANG DI KECAMATAN BUKIT TUSAM, KABUPATEN ACEH TENGGARA - Yassir, Muhammad; Fathiya, Nir; Nursafiah, Nursafiah; Wiljanatunnisa, Wiljanatunnisa; Puspita, Diah Eka; Akram, Habibul; Ramut, Anuar (FKIP Universitas Tanjungpura, 2025)
Traditional knowledge of rhizomatous plant species is gradually declining, particularly among younger generations. This study aims to inventory the rhizome plant species found in Bukit Tusam District, Southeast Aceh Regency, in order to support conservation efforts and promote local botanical literacy. A qualitative descriptive approach was used, employing field observations and purposive sampling. Seven rhizomatous species from the family Zingiberaceae were identified: Zingiber officinale (ginger), Kaempferia galanga (kaempferia), Boesenbergia rotunda (temukunci), Curcuma longa (turmeric), Alpinia galanga (galangal), Curcuma xanthorrhiza (Javanese turmeric), and Zingiber cassumunar (bangle). These findings contribute to the documentation of local plant diversity and highlight the importance of preserving ethnobotanical knowledge for future generations.